Spathodea campanulata (Bignoniaceae): flower visitors and nectar characteristics. - RIBEIRO, M. de F. (2018)
Spathodea campanulata is an exotic plant often used in arborisation of Brazilian cities.Its flower resources are toxic for insects, including bees. In order to investigate this westudied a tree located at Embrapa Semiárido (Petrolina) in July-August 2017-2018.